Sistem Pengelolaan Rekam Medik Pada Rumah Sakit Umum Daerah Merauke - Farida Romaito Pohan; Febiyanti Karaeng (Jurnal Administrasi Karya Dharma, 2022)
The medical record is one part of the hospital which has duties including recording, data processing, and reporting of information needed for activities in the hospital. The process of processing medical records from the Assembling, Coding, Indexing, Analyzing, and Filling sections has an effect on improving the quality of medical records in hospitals. This study aims to find out more about the problem of the medical record management system at the Merauke District General Hospital and what factors support and hinder the process of managing medical record files at the Merauke District General Hospital. The research method used in this study is a qualitative method. The results of the study indicate that the medical record management system at the Merauke District General Hospital is quite good. This can be seen from the fulfillment of management system indicators, which include input components, process components, and output components.